Temperature and pH affect the production of bacterial biofilm - Hostacká, A; Ciznár, I; Stefkovicová, M (Folia microbiologica, 2010)
The effect of different cultivation temperatures (30 and 37 degrees C) and pH of the media (5.5, 7.5, 8.5) on the biofilm production was compared in Pseudomonas aeruginosa, Klebsiella pneumoniae, and Vibrio cholerae non-O1 and O1 using the crystal-violet test for estimation of quantitative production of the biofilm. Decrease (46.4-98.4 %) in the biofilm production was observed at 37 degrees C in 8 of the tested strains (P. aeruginosa three strains, K pneumoniae two, V. cholerae non-O1 two, and V. cholerae O1 one strain) compared with the production at 30 degrees C. On the other hand, five strains (P. aeruginosa 1, K. pneumoniae 3, V. cholerae non-O1 1) exhibited under these conditions a higher biofilm production (103-143 %). However, this difference was not significant (p = 0.196). Increased pH lead to a higher biofilm production using all media tested. In P. aeruginosa the biofilm production at pH 8.5 was 139-244 %, at pH 7.5 136-164 % in comparison with pH 5.5. Similarly, in K. pneumoniae the biofilm production increased to 151-319 % at pH 8.5 while with the drop of pH to 7.5 the biofilm production was 113-177 % compared with pH 5.5. In V. cholerae non-O1 and O1 the biofilm production reached 204-329 % at pH 8.5, and 123-316 % at pH 7.5 (compared with the production at pH 5.5). An increase in biofilm production represented an average of 169 % (p = 0.001) at pH change from 5.5 to 7.5, with the rise of pH from 5.5 to 8.5 caused an average difference of 229 % (p = 0.001).
Keywords: financování organizované; genciánová violeť; Hydrogen-Ion Concentration; teplota; Staining and Labeling; lidé; Coloring Agents; Vibrio cholerae non-O1; barvení a značení; Financing, Organized; Temperature; Pseudomonas aeruginosa; barvicí látky; Gentian Violet; biofilmy; Vibrio cholerae O1; koncentrace vodíkových iontů; Klebsiella pneumoniae; Biofilms; Humans